Amido‐Triazole Complexes, “Normal” Triazole‐Based Imines and Metallo‐Mesoionic Imines - M. Sc. Richard Rudolf; Prof. Dr. Biprajit Sarkar (ChemistryEurope)
Abstract Mesoionic compounds are hugely popular in fields such as organic chemistry, organometallic chemistry and homogeneous catalysis. A new sub‐class are the mesoionic imines (MIIs). We present here 5‐amino‐4‐pyridyl‐1,2,3‐triazole as a new and versatile synthon for generating first examples of metallo‐MIIs. In this approach, we make use of metallation at the N‐pyridyl/N3‐triazole chelating pocket (instead of quarternisation of N3‐triazole) and subsequent deprotonation to generate highly versatile and tunable metallo‐MIIs. These unprecedented metallo‐MIIs contain a highly nucleophilic N‐donor site, and a tunable electrophilic metal site. Apart from displaying strong and directed H‐bonding interactions like their “classical” MII analogues, the metallo‐MIIs engage in aromatic C−F activation as well as meta−C−H activation reactions. Facile synthesis of homo and heterodincuelar complexes which contain a mixed coordinative saturation/unsaturation with these metallo‐MIIs is presented. Apart from the metallo‐MIIs we have also used 5‐amino‐4‐pyridyl‐1,2,3‐triazole as a precursor to generate the first examples of amido‐1,2,3‐triazole complexes and the first example of a “normal” (and not mesoionic) 1,2,3‐triazole based imine. Our results establish metallo‐MIIs as a versatile new class of mesoionic compounds that combine the modularity of click reactions, with the functionality of metal fragments to generate electronically ambivalent compounds with a huge potential in synthetic chemistry, catalysis and beyond.